Analisis kemampuan represenasi matematis siswa MAN II Kota Batu pada materi deret geometri - Mohammad Archi Maulyda; Ratna Yulis Tyaningsih; Baidowi Baidowi (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2019)
The representation ability possessed by students is one of the key factors in learning mathematics in schools. Because it needs a study to understand how the ability of representation of students when given a problem. The purpose of this study is to describe the mathematical representation ability of students in class XI IPA MAN II Batu on geometrical series material. For this reason, the research conducted is a qualitative research with a descriptive approach so that researchers can describe how the students' representational abilities. Students are grouped in the ability category of high (KT), moderate (KS), and low (KR). The results of this study are KT, KS, and KR have not met the indicators of the ability of representation that has been determined. The non-fulfillment of these indicators is due to a mismatch between external representation and internal representation.